Pengaruh Profitabilitas, Komite Audit dan Kepemilikan Asing Terhadap Kebijakan Dividen (Studi pada Perusahaan Properti, Real Estate dan Konstruksi Bangunan yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2018) - Awiah Fitriyani (UPT Penerbitan Universitas Jember, 2020)
This study aims to determine the effect of profitability as measured by return on equity, audit committee and foreign ownership on dividend policy as measured by dividend payout ratio. So sample used in research this as many as 45 samples, consistingfom 9 companies registered in the property, real estate, construction and building companies listed on the Indonesia Stock Excange with period years 2014-2018. The results of this study indicate that partially Return on Equity significantly influences the Dividend Payout Ratio, the Audit Committee does not significantly influence the Dividend Payout Ratio and Foreign Ownership has a significant effect on the Dividend Payout Ratio. In addition, the results of the simultaneous study that Return on Equity, Audit Committee and Foreign Ownership of Dividend Payout Ratio have a significant effect on Dividend Payout Ratio.